Impact of socioeconomic status on cancer staging, survival in non-small cell lung cancer - Yang, Xianghui; Deng, Liyong; Li, Min; Zhou, Yongjie; Wang, Guihua (Frontiers in Public Health, 2022)
Purpose: We performed this study to evaluate the association of socioeconomic status (SES) factors with cancer-specific survival (CSS) of patients with non-small cell lung cancer (NSCLC). We further assessed the predictive value of a novel Tumor Node Metastasis (TNM)-SES staging system, combining the TNM stage with the SES stage. Methods: Using the Surveillance, Epidemiology, and End Results (SEER) database, we selected 40378 patients diagnosed with NSCLC from 2012 to 2016. Cox regression method and Harrell's concordance index (C-index) were performed to select the SES factors related to CSS and evaluate the predictive ability of the novel TNM-SES stage. We used Kaplan–Meier curves and a log-rank test to conduct a survival analysis. Results: We identified four SES factors (marriage, insurance, education and household income) associated with CSS and constructed the SES stage (SES-1 and SES-2). NSCLC patients with SES-2 stage (low SES) was associated with young adult, black race, male, squamous carcinoma, upper lobe site and advanced stage.SES-2 stage patients were significantly associated with a dismal prognosis of patients with NSCLC, with a 21.0% increased risk (HR=1.21, 95%CI (1.18-1.24), p < 0.001). The C-index of our novel TNM-SES stage was 0.732 (95%CI(0.728-0.736)), higher than the traditional TNM stage (0.717，95%CI(0.715-0.719）)， indicating superior predictive value. Conclusion: Our population-based study indicated that SES was significantly associated with cancer staging and SCC in patients with NSCLC. Our novel TNM-SES staging system showed a superior predictive value to the traditional TNM stage. The impact of SES on patients with NSCLC should receive more concern in clinical management.